Biomarker value and pitfalls of serum S100B in the follow-up of high-risk melanoma patients - Gebhardt, Christoffer; Lichtenberger, Ramtin; Utikal, Jochen (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Background and objectives Serum levels of S100B are standard in monitoring advanced malignant melanoma patients in order to discriminate progressive from non-progressive disease. False-positive results lead to distress among patients and increase the amount of cost-intensive diagnostics. We therefore analyzed reported comorbid diseases as putative sources of excessive S100B release. Patients and methods Here, we report a single-center experience on serum S100B levels in 2,664 blood samples from 1,113 stage IB to IV melanoma patients (AJCC) who presented for follow-up examinations over a period of 24 months. Results Overall, 295 (11 %) of patients developed disease progression. In patients with a high tumor load, the rate of false-negative results was 30/185 (16 %). The rate of false-positive results was 247/2369 (12 %). One hundred and six false-positive results (69 %) compared to 46 true-positive results (31 %) were found in patients with cardiovascular diseases such as arrhythmia (50/32) or previous myocardial infarction (22/14). Moreover, obesity (85/14), liver cirrhosis (31/10), migraine (18/2), chronic kidney disease (13/2), and previous stroke (11/1) were found to be associated with false-positive S100B levels. Conclusions Serum S100B is a useful quantitative biomarker in routine follow-up of high-risk melanoma patients. While false-negative results are frequent in patients with low tumor load, false-positive results are associated with several comorbid diseases and warrant careful reevaluation.